Prenatal Sacrococcygeal Teratoma Diagnosed in a Fetus with Partial Trisomy 13q22 - Shana S. Dalal; Teresa Berry; Veronica Maria Pimentel (Hindawi Limited, 2019)
Sacrococcygeal teratoma is a rare neoplasm that arises from a totipotent stem cell in Henson's node. It has rarely been associated with chromosomal abnormalities. We present a unique case of a 25-year-old primigravida at 19 weeks and 5 days of gestation found to have an exophytic complex mass with cystic and solid components in the sacral region. This mass was consistent with a sacrococcygeal teratoma. The patient had originally declined genetic screening. After the ultrasound and genetic counseling, she opted to have cell-free fetal DNA screening that was positive for Trisomy 13. Amniocentesis was performed to confirm the diagnosis. The karyotype demonstrated an abnormality of chromosome 13 and microarray demonstrated a complex structural abnormality of chromosome 13 with large regions of copy number gain. The patient underwent a dilation and evacuation at 23 weeks and 2 days. No fetal autopsy was done. This is a case of a prenatally diagnosed sacrococcygeal teratoma associated with Trisomy 13. It illustrates the diagnostic importance of amniocentesis in setting of fetal anatomical abnormalities on ultrasound. For patients who are reluctant to undergo amniocentesis, cell-free DNA results may provide the additional evidence of the need for diagnostic tests.